Financing instruments and challenges for innovation in the EU: Panel evidence from the SAFE survey - Alessio Mitra; Valentina Di Girolamo; Erik Canton (Publications Office of the European Union, 2023)
This paper studies the firm-level drivers of product, process, organisation and marketing innovation in the EU with panel data from 2009 to 2021. Employing conditional logit and linear probability models we investigate how firms' characteristics, firms' sources of financing, and firm perception of different challenges influence their likelihood to innovate. In line with the academic literature, we find that firms' size and profit level improve firms' innovation performance, while firms' age decreases it. We also observe that the effectiveness of different financing instruments varies considerably depending on whether the company is pursuing product, process, organisation or marketing innovation. Finally, innovative firms more frequently report access to finance and regulations as important challenges for their future, while the relevance of other challenges (e.g. the availability of skilled staff or finding customers) varies depending on what type of innovation activities companies are engaged in.
Keywords: G20; G23; O30; 330; Access to finance; Financing instruments; Innovation challenges; Firm innovation